Comparative study of biorefinery processes for the valorization of fast-growing Paulownia wood. (October 2020) - del Río, Pablo G.; Domínguez, Viana D.; Domínguez, Elena; Gullón, Patricia; Gullón, Beatriz; Garrote, Gil; Romaní, Aloia
Highlights: Three process configurations were proposed for the fractionation of Paulownia wood. Autohydrolysis allowed to solubilize 85% of hemicellulosic compounds. Organosolv delignification was suitable to release up to 71% of the lignin. Combination of both processes enables suitable recovery of all Paulownia fractions. High ethanol titer (64 g/L) was obtained from pretreated wood by combined processes. Abstract: In this work, valorization of Paulownia wood (PW) was proposed following several process configurations for biofuels and value-added compounds production. Firstly, autohydrolysis and ethanol-organosolv strategies were assessed separately for the fractionation of PW to enhance the enzymatic digestibility of cellulose. A third strategy focused on a sequential process (autohydrolysis and organosolv) was explored. Two temperatures were selected for the first stage of the combined process. High concentration of oligosaccharides (26.29 g/L) and high concentration of degradation products (17.21 g/L) were obtained at 210 and 230 °C, respectively. The solids obtained from both pretreatments were subjected to organosolv delignification (200 °C, 3 h and 50% ethanol) achieving delignification of 58 and 30% for the autohydrolyzed biomass at 210 °C and 230 °C, respectively. The combined process resulted in susceptible biomass able to produce 64 g/L of ethanol. Therefore, the strategies explored in this work open the possibility to build a refinery around Paulownia wood.